Asuhan Kebidanan pada Ibu Menyusui dengan Pemberian Terapi Buah Pepaya untuk Meningkatkan Produksi ASI - Dwi Astuti; Sarkiah Sarkiah; Luthfia Hidayati Rahman; Nurul Hidayah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the effectiveness of midwifery care for breastfeeding mothers using papaya therapy to increase breast milk production. The study used an observational case study with a qualitative approach. The results showed that on the third day after 7 days of regular consumption of papaya, breast milk volume increased significantly, from 100 ml on D-1 to 610 ml on D-7. The mother's rest pattern before the intervention was 6 hours, and after the intervention, it increased to 8 hours. In conclusion, papaya therapy is effective in significantly increasing breast milk production in breastfeeding mothers. This intervention can be a simple and easy-to-implement alternative to support exclusive breastfeeding. Keywords: Breast Milk, Papaya, Breastfeeding Mothers